A STUDY ON IDENTIFICATION AND GEOCHEMICAL PROPERTIES OF HEAVYMETALS IN SOIL (International Journal of Food and Nutritional Sciences, 2022)
In the recent Era, due to the rapid growth of Urbanization, Industrialization, Mining activity the pollution problem arises in tremendous way. The effects of the heavymetals in soil, water and sediments were the main focal theme of the all the current researchers. An environmental geochemical investigation was carried out in industrial area of the Mysuru city to assess the contamination of the heavymetals in the different fraction and the extent of chemical contamination in soil. The purpose of this study was to assess the chemical partitioning of selected heavy metal in soil and to assess the degree of pollution in the study area. A five-step sequential extraction technique was used to assess the environmental status of heavy metals. Most of metals were considered to be mobile due to the ionic movement. The seasonal variations of heavy metals was observed and found slightly higher in summer than in monsoon season due to the dilution factor. The result shown of heavy metal concentrations reveal that the industrial area soil is highly contaminated due to improper disposal of solid waste, hazardous waste and improper treatment of effluent.